Dissecting the bidirectional associations between the progression of gastrointestinal and endocrine diseases - Liu, Hongyan; Si, Shucheng; Zhang, Hua; Zhan, Siyan (Frontiers in Endocrinology, 2025)
BackgroundsThe widespread intrinsic link between gastrointestinal and endocrine diseases was poorly understood. We aimed to dissect the bidirectional association in the progression of gastrointestinal with endocrine diseases, either the overall, individual, or comorbidities with each other.MethodsA bidirectional-designed prospective cohort included 481841 and 452858 participants free of gastrointestinal and endocrine diseases at baseline in the UK Biobank. Multivariable Cox proportional hazard models were used to estimate the hazard ratios (HRs) and 95% confidence interval (CI) for incident endocrine diseases according to gastrointestinal disease status or the number of gastrointestinal comorbidities, and vice versa.ResultsOverall gastrointestinal disease was associated with an increased risk of incident endocrine diseases (HR, 1.22; 95% CI, 1.19-1.25), and conversely, overall endocrine disease also increased the risk of total gastrointestinal diseases (HR, 1.48; 95% CI, 1.44-1.53). For specific diseases, extensive bidirectional associations were observed between type 2 diabetes and six gastrointestinal diseases (gastritis and duodenitis, irritable bowel syndrome, gastrointestinal hemorrhage, dyspepsia, duodenal ulcer, and gastric ulcer), thyroid disorders, and five gastrointestinal diseases (gastritis and duodenitis, irritable bowel syndrome, dyspepsia, malabsorption, and ulcerative colitis), hyperparathyroidism and three gastrointestinal diseases (gastritis and duodenitis, gastrointestinal hemorrhage, and duodenal ulcer), etc. The risk of overall endocrine (HR, 1.14; 95% CI, 1.12-1.16) and gastrointestinal diseases (HR, 1.50; 95% CI, 1.46-1.55) increased with per-comorbidity increasing. This trend was similarly observed for most individual diseases.ConclusionsWe observed an extensive bidirectional association in overall, specific, and number of comorbidities between gastrointestinal and endocrine diseases.